Coated cutting tools

JP7940004B2Active Publication Date: 2026-10-22SANDVIK COROMANT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024516477
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-17
Filing Date
2022-09-08
Publication Date
2026-10-22
Estimated Expiration
2042-09-08

Smart Images

  • Figure 0007940004000005
    Figure 0007940004000005
  • Figure 0007940004000006
    Figure 0007940004000006
  • Figure 0007940004000007
    Figure 0007940004000007
Patent Text Reader

Abstract

The present invention relates to a coated cutting tool (1) comprising a substrate (5) and a coating (6), the coating (6) being Ti 1-x Al x The first nanolayer type (9), which is N (0.35≦x<0.67), Ti 1-y S y A second nanolayer type (10) in which y is 0.10≦y≦0.25, and Ti 1-z Al z a nanolayer (8) of about 0.5 to about 10 μm of alternating nanolayers of a third nanolayer type (11) having a thickness of 0.70≦z≦0.90, wherein each nanolayer type Ti in the nanolayer (8) 1-x Al x N(9), Ti 1-y S y N(10), and Ti 1-z Al z The present invention relates to a coated cutting tool (1) having an average nanolayer thickness of N(11) of 1 to 30 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention, Ti 1-x Al x N(0.35≦x<0.67), Ti 1-y Si y N(0.10≦y≦0.25), and Ti 1-z Al z This relates to a coated cutting tool that includes a coating containing a nanomultilayer coating with alternating nanolayers of N(0.70≦y≦0.90). [Background technology]

[0002] Metal machining operations include, for example, turning, milling, and drilling. To provide long tool life, coated cutting tools, such as inserts, should have high resistance to various types of wear. Various types of wear-resistant coatings are known in the art to enhance the wear resistance of cutting tools.

[0003] A cutting tool generally has at least one rake face and at least one flank face. The cutting edge is located where the rake face and the flank face intersect.

[0004] Flank wear is primarily due to the abrasive wear mechanism and is clearly observed on the flank surface of the cutting edge. The flank surface is subjected to the movement of the workpiece, and excessive flank wear leads to insufficient surface texture of the workpiece, resulting in an inaccurate cutting process and increased friction during the cutting process.

[0005] When better flank wear resistance is provided, it results in longer tool life for certain metal machining operations.

[0006] The coating must also remain attached to the substrate during machining operations; that is, it must not peel off. Some workpiece material types, such as ISO-M (stainless steel) and ISO-S (heat-resistant superalloys and, for example, titanium), are so-called adhesive materials and are more prone to peeling than other workpiece material types. These material types also exhibit smearing behavior, which means that the workpiece material rubs against the cutting tool surface, thereby potentially forming a built-up edge (BUE) of the workpiece material on the cutting edge. Such a BUE can cause the coating to peel off, or even cause a portion of the cutting edge of the cutting tool to detach.

[0007] Various metal machining operations affect coated cutting tools in different ways. Turning, for example, is a continuous metal machining operation, while milling is inherently more intermittent. In milling, thermal and mechanical loads change over time. Thermal loads induce thermal tension that can lead to so-called thermal cracks (referred to herein as "comb cracks") within the coating, while the latter can cause fatigue at the cutting edge, resulting in chipping, i.e., small fragments of the cutting edge separating from the rest of the material. Therefore, the common wear types of coated cutting tools in milling are cracking and chipping. Such chipping can be reduced by a high level of toughness of the coating, especially at the cutting edge. Therefore, high resistance to comb cracks and edge toughness are very important for tool life.

[0008] To provide cutting tools with superior properties compared to currently available cutting tools on the market, there is a continuing demand for coated cutting tools with coatings that offer superior characteristics in terms of wear resistance, edge toughness, comb crack resistance, and peel resistance. Improving one or more of the above characteristics results in a longer tool life.

[0009] Nanoscale multilayer coatings are used in the field of cutting tools for metal machining. In these coatings, at least two layers that differ in some respect alternately form a coating of a stack of nanolayers. SUMMARY OF THE INVENTION

[0010] An object of the present invention is to provide a coated cutting tool that at least exhibits high flank wear resistance and high peeling resistance.

[0011] The object of the present invention is achieved by a coated cutting tool comprising a substrate and a coating, wherein the coating is Ti 1-x Al x N (0.35≦x<0.67) as a first nanolayer type, Ti 1-y Si y N (0.10≦y≦0.25) as a second nanolayer type, and Ti 1-z Al z N (0.70≦z≦0.90) as a third nanolayer type, comprising a nanoscale multilayer of about 0.5 to about 10 μm of alternating nanolayers, wherein the average nanolayer thickness of each nanolayer type Ti in the nanoscale multilayer 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z N is 1 to 30 nm, by the coated cutting tool.

[0012] As used herein, "the nanoscale multilayer of alternating nanolayers of the first nanolayer type, the second nanolayer type, and the third nanolayer type" means that different types of nanolayers are generally alternating in a specific order in the nanoscale multilayer. However, due to the method selected for depositing the nanoscale multilayer in a PVD reactor, for example, using the so-called three-fold rotation of the tool to be coated, there may be a change in the order of the three types of nanolayers at several locations within the nanoscale multilayer.

[0013] In one embodiment, the ratio between the sum of all nanolayer thicknesses of each nanolayer type in the nanomultilayer, Ti 1-x Al x N:Ti 1-y Si y N:Ti 1-z Al z N is a:b:c [wherein 0.5<a<3, 0.5<b<3, 0.5<c<3, preferably 0.75<a<2.5, 0.75<b<2.5, 0.75<c<2.5, most preferably 0.9<a<2.25, 0.9<b<2.25, 0.9<c<2.25].

[0014] The ratio between the sum of the nanolayer thicknesses of each nanolayer type in the nanomultilayer, Ti 1-x Al x N:Ti 1-y Si y N:Ti 1-z Al z N, i.e., a:b:c, can be determined by scanning transmission electron microscopy (STEM) analysis, preferably in combination with energy-dispersive X-ray spectroscopy (EDS), over a distance perpendicular to the substrate surface, where the elemental composition and the thickness of individual nanolayers are determined. A distance of at least 25 times the average nanolayer thickness is used. The sum of the nanolayer thicknesses of the nanolayers of the first nanolayer type Ti 1-x Al x N is "a", the sum of the nanolayer thicknesses of the nanolayers of the second nanolayer type Ti 1-y Si y N is "b", and the sum of the nanolayer thicknesses of the nanolayers of the third nanolayer type Ti 1-z Al z N is "c".

[0015] The average nanolayer thickness of each nanolayer type Ti in the nanomultilayer 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z N can also be determined by the STEM / EDS analysis described above.

[0016] The first nanolayer type is Ti 1-xAl x is N, suitably 0.40≦x≦0.67, and preferably 0.45≦x≦0.62.

[0017] The second nanolayer type is Ti 1-y Si y is N, suitably 0.13≦y≦0.23, and preferably 0.17≦y≦0.21.

[0018] The third nanolayer type is Ti 1-z Al z is N, suitably 0.70<z≦0.85, and preferably 0.75<z≦0.85.

[0019] The average nanolayer thickness of each nanolayer type Ti 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z N in the nanomultilayer is suitably 1 to 20 nm, preferably 1.5 to 10 nm, and most preferably 2 to 5 nm.

[0020] In the nanomultilayer, the ratio of the average nanolayer thickness in the nanomultilayer between any one of the nanolayer types Ti 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z N and any one of the remaining two of the nanolayer types Ti 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z N is suitably 0.1 to 10, preferably 0.5 to 5, and most preferably 0.8 to 2.

[0021] Suitably, within a series of 10 consecutive nanolayers, preferably 8, and most preferably 6 consecutive nanolayers in the nanomultilayer, the nanolayer type Ti 1-x Al x N, Ti1-y Si y N and Ti 1-z Al z All of N exist.

[0022] The thickness of the nanolayer is appropriately about 1 to about 8 μm, preferably about 1.5 to about 5 μm.

[0023] In one embodiment, the coating includes an inner layer of TiN or (Ti,Al)N beneath the nanomultilayer, preferably closest to the substrate. The (Ti,Al)N layer may be a single layer or a nanomultilayer of alternating nanolayers with different Ti / Al ratios. Preferably, the inner layer is (Ti,Al)N. When (Ti,Al)N is used as the inner layer, (Ti,Al)N is appropriately Ti 1-t Al t N is (0.35 ≤ t ≤ 0.67, preferably 0.40 ≤ t ≤ 0.67, most preferably 0.45 ≤ t ≤ 0.62). In a preferred embodiment, the Ti-Al relationship in the inner layer (Ti,Al)N is the same as the Ti-Al relationship in the first nanolayer type of nanomultilayer. This simplifies manufacturing if the same target already used in the nanomultilayer can be used. The thickness of this inner layer is appropriately about 0.1 to about 3 μm, preferably about 0.5 to about 2 μm.

[0024] In one embodiment, for the purpose of controlling the color of the coated cutting tool, the coating is a first nanolayer type Ti 1-x Al x N(0.35≦x<0.67), second nanolayer type Ti 1-y Si y N(0.10≦y≦0.25), or third nanolayer type Ti 1-z Al z It includes one of the outermost single layers N(0.70≦z≦0.90).

[0025] The x, y, or z values ​​of the outermost layer are preferably those of a nanolayer Ti. 1-x Al x N, Ti 1-y Siy N, or Ti 1-z Al z This is the same as x, y, or z of N. This simplifies manufacturing if the same targets already used in nanolayers can be used.

[0026] The thickness of this outermost layer is appropriately about 0.1 to about 0.5 μm, preferably about 0.1 to about 0.3 μm.

[0027] The nanolayers of the first, second, and third nanolayer types are appropriately cathode arc evaporation deposits. Additionally, the optionally selected inner layers of TiN or (Ti,Al)N, as well as the optionally selected outermost single layer, are appropriately cathode arc evaporation deposits.

[0028] The base material for the coated cutting tool can be selected from the group consisting of cemented carbide, cermet, ceramic, cubic boron nitride, and high-speed steel. In one embodiment, the base material is a cemented carbide containing 5 to 18% by weight of Co.

[0029] Coated cutting tools are, appropriately, cutting tool inserts, drills, or solid end mills for metal machining. Cutting tool inserts are, for example, turning inserts or milling inserts. [Brief explanation of the drawing]

[0030] [Figure 1] This is a schematic diagram showing one embodiment of a cutting tool, which is a milling insert. [Figure 2] This is a schematic diagram showing one embodiment of a cutting tool that is a turning insert. [Figure 3] This is a schematic diagram showing a cross-section of one embodiment of a coated cutting tool of the present invention, which includes a base material and a coating comprising different layers. [Modes for carrying out the invention]

[0031] Detailed Description of the Embodiments in the Drawings Figure 1 shows a schematic view of an embodiment of a cutting tool (1) having a rake face 2, a flank face 3, and a cutting edge 4. In this embodiment, the cutting tool 1 is a milling insert. Figure 2 shows a schematic view of an embodiment of a cutting tool 1 having a rake face 2, a flank face 3, and a cutting edge 4. In this embodiment, the cutting tool 1 is a turning insert. Figure 3 shows a schematic cross-sectional view of an embodiment of the coated cutting tool of the present invention having a substrate 5 and a coating 6. The coating 6 comprises a first (Ti,Al)N innermost layer 7, followed by Ti 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z N, consisting of a nanomultilayer 8 of alternating nanolayers 9, 10, and 11.

[0032] In one embodiment, the ratio a:b:c in the nanomultilayer 8, which is the ratio between the sum of the nanolayer thicknesses of each nanolayer type 9, 10, 11 in the nanomultilayer 8, of Ti 1-x Al x N:Ti 1-y Si y N:Ti 1-z Al z N, satisfies 1.5<a<2.5, 0.75<b<1.25, 0.75<c<1.25, preferably 1.75<a<2.25, 0.9<b<1.1, 0.9<c<1.1. In this embodiment, the nanomultilayer 8 is suitably Ti 1-x Al x N / Ti 1-z Al z N / Ti 1-x Al x N / Ti 1-y Si y N in the order of the first nanolayer type 9, which is Ti 1-x Al x N, the second nanolayer type 10, which is Ti 1-y Si y N, and the third nanolayer type 11, which is Ti 1-z Al zincludes a repeating sequence of N consecutive nanolayers. The nanomultilayer 8 is suitably (Ti 1-x Al x N / Ti 1-z Al z N / Ti 1-x Al x N / Ti 1-y Si y N..) m and is composed of, where m=15~1500, suitably m=30~800.

[0033] In a further embodiment, there is a Ti with a:b:c ratio in the nanomultilayer 8, which is the ratio in the nanomultilayer 8 between the sum of the nanolayer thicknesses of each nanolayer type 9, 10, 11 in the nanomultilayer 8 1-x Al x N:Ti 1-y Si y N:Ti 1-z Al z N, where 0.75<a<1.25, 1.5<b<2.5, 0.75<c<1.25, preferably 0.9<a<1.1, 1.75<b<2.25, 0.9<c<1.1. In this embodiment, the nanomultilayer 8 is suitably Ti 1-x Al x N / Ti 1-y Si y N / Ti 1-z Al z N / Ti 1-y Si y N in the order of, the first nanolayer type 9 being Ti 1-x Al x N, the second nanolayer type 10 being Ti 1-y Si y N, and the third nanolayer type 11 being Ti 1-z Al z N, includes a repeating sequence of consecutive nanolayers. The nanomultilayer (8) is suitably (Ti 1-x Al x N / Ti 1-y Si y N / Ti 1-z Al z N / Ti 1-y Si y N) n and is composed of, where n=15~1500, suitably n=30~800.

[0034] In a further embodiment, the ratio a:b:c in the nanomultilayer 8 between the sum of the nanolayer thicknesses of each nanolayer type 9, 10, 11 in the nanomultilayer 8 is Ti 1-x Al x N:Ti 1-y Si y N:Ti 1-z Al z N, where 0.75<a<1.25, 0.75<b<1.25, 1.5<c<2.5, preferably 0.9<a<1.1, 0.9<b<1.1, 1.75<c<2.25. In this embodiment, the nanomultilayer 8 is suitably Ti 1-z Al z N / Ti 1-x Al x N / Ti 1-z Al z N / Ti 1-y Si y N in order, comprising a repeating sequence of successive nanolayers of Ti 1-x Al x N as the first nanolayer type 9, Ti 1-y Si y N as the second nanolayer type 10, and Ti 1-z Al z N as the third nanolayer type 11. The nanomultilayer 8 suitably comprises (Ti 1-z Al z N / Ti 1-x Al x N / Ti 1-z Al z N / Ti 1-y Si y N) p , where p=15~1500, suitably p=30~800.

[0035] In a further embodiment, the ratio a:b:c in the nanomultilayer 8 between the sum of the nanolayer thicknesses of each nanolayer type 9, 10, 11 in the nanomultilayer 8 is Ti 1-x Al x N:Ti 1-y Si y N:Ti 1-z Al zN, 0.75<a<1.25, 0.75<b<1.25, 0.75<c<1.25, preferably 0.9<a<1.1, 0.9<b<1.1, 0.9<c<1.1. In this embodiment, the nanomultilayer 8 is suitably Ti 1-x Al x N / Ti 1-y Si y N / Ti 1-z Al z N in the order of a repeating sequence of successive nanolayers of Ti 1-x Al x N as the first nanolayer type 9, Ti 1-y Si y N as the second nanolayer type 10, and Ti 1-z Al z N as the third nanolayer type 11. The nanomultilayer 8 suitably comprises (Ti 1-x Al x N / Ti 1-y Si y N / Ti 1-z Al z N) q , where q=20 to 2000, suitably q=40 to 1000.

[0036] In a further embodiment, the coating 6 comprises an inner layer 7 of (Ti,Al)N below the nanomultilayer 8, preferably closest to the substrate 5, and the inner layer 7 is a (Ti,Al)N layer which is a (Ti,Al)N nanomultilayer of alternating nanolayers of Ti 1-u Al u N (0.35≦u<0.67, suitably 0.40≦u≦0.67, preferably 0.45≦u≦0.62) and Ti 1-v Al v N (0.70≦v≦0.90, suitably 0.70≦v≦0.80).

[0037] The average nanolayer thickness of the Ti 1-u Al u N layers in the (Ti,Al)N nanomultilayer is suitably 1 to 30 nm, preferably 1 to 20 nm, most preferably 2 to 10 nm. The thickness of this inner layer 7 is suitably from about 0.1 to about 3 μm, preferably from about 0.5 to about 2 μm. Examples

[0038] Example 1 (The present invention) Ti deposited on sintered cemented carbide cutting tool insert blanks of the shapes CNMG120408MM and R390-11T308M-PM 0.85 Si 0.15 N, Ti 0.50 Al 0.50 N and Ti 0.20 Al 0.80 We provided a cutting tool coated with a nanolayer containing N nanolayers. The cemented carbide composition was 10 wt% Co, 0.4 wt% Cr, and the residue WC. The cemented carbide blank was coated by cathode arc evaporation in a vacuum chamber containing four arc flanges (each flange containing multiple cathode evaporators). 0.50 Al 0.50 The target was installed inside the evaporator at two of the opposing flanges. The remaining target was Ti 0.85 Si 0.15 and Ti 0.20 Al 0.80 The targets were mounted inside the evaporator on the remaining two flanges, which faced each other. The targets were circular and planar, with a diameter of 100 mm, which is readily available on the market. Suitable target technology packages for arc evaporation are available from market suppliers such as IHI Hauzer Techno Coating BV, Kobelco (Kobe Steel Ltd.), and Oerlikon Balzers.

[0039] An uncoated blank was mounted on a pin that underwent three rotations within a PVD chamber.

[0040] Chamber in high vacuum (10 -2 The plasma was pumped down to less than Pa and heated to approximately 450-550°C by a heater located inside the chamber. The blank was then etched in Ar plasma for 60 minutes.

[0041] First, 0.50 Al 0.50 By using only the target, Ti 0.50 Al 0.50 The innermost layer of N was deposited.

[0042] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -50 V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150 A for 70 minutes (each) (two flanges). The table rotation speed was 5 rpm. Ti with a thickness of approximately 1.4 μm. 0.50 Al 0.50 A layer of N was deposited on the blank.

[0043] Next, nanolayers were deposited by using all of the attached targets.

[0044] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -70 V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150 A for 35 minutes each (four flanges). The table rotation speed was 5 rpm. A nanomultilayer coating with a thickness of approximately 1.4 μm was deposited on the blank.

[0045] The rotation speed correlates with the thickness of a particular stage, and the current deposition rate and the table rotation speed of 5 rpm for the equipment used correlate with each nanolayer Ti 0.50 Al 0.50 N, Ti 0.85 Si 0.15 N and Ti 0.20 Al 0.80 It was concluded that there is a correlation with the average individual nanolayer thickness of N, which is approximately 2 nm. The number of nanolayers in the nanomultilayer is approximately 700.

[0046] Nano multilayers are made of Ti 0.50 Al 0.50 N / Ti 0.20 Al 0.80N / Ti 0.50 Al 0.50 N / Ti 0.85 Si 0.15 The sequence includes repeating sequences of continuous nanolayers in the order N.

[0047] Finally, to obtain a uniform color among the individually coated cutting tools that were fabricated, Ti 0.85 Si 0.15 By using only the target, Ti 0.85 Si 0.15 The outermost layer of N was deposited. All deposition parameters were the same as when depositing the previous layer (one flange), except that the bias was -60V and the cathode was operated for 10 minutes. 0.85 Si 0.15 A layer of N was deposited to a thickness of approximately 0.2 μm.

[0048] In a nanomultilayer, each nanolayer Ti 0.50 Al 0.50 N, Ti 0.85 Si 0.15 N, Ti 0.20 Al 0.80 The ratio of the total thickness of each nanolayer in N, i.e., Ti 0.50 Al 0.50 N:Ti 0.85 Si 0.15 N:Ti 0.20 Al 0.80 N is approximately 2:1:1. This ratio is estimated from the assumed equal deposition rates from each target, rotation during deposition, and deposition time.

[0049] The coated cutting tool is referred to as "Sample 1 (the present invention)".

[0050] Example 2 Ti deposited on sintered cemented carbide cutting tool insert blanks of the shapes CNMG120408MM and R390-11T308M-PM 0.85 Si 0.15 N, Ti 0.50 Al 0.50 N and Ti 0.20 Al 0.80We provided a cutting tool coated with a nanolayer containing N nanolayers. The cemented carbide composition was 10 wt% Co, 0.4 wt% Cr, and the residue WC. The cemented carbide blank was coated by cathode arc evaporation in a vacuum chamber containing four arc flanges (each flange containing multiple cathode evaporators). 0.50 Al 0.50 The target was installed inside the evaporator at two of the opposing flanges. The remaining target was Ti 0.85 Si 0.15 and Ti 0.20 Al 0.80 The targets were mounted inside the evaporator on the remaining two flanges, which faced each other. The targets were circular and planar, with a diameter of 100 mm, which is readily available on the market. Suitable target technology packages for arc evaporation are available from market suppliers such as IHI Hauzer Techno Coating BV, Kobelco (Kobe Steel Ltd.), and Oerlikon Balzers.

[0051] An uncoated blank was mounted on a pin that underwent three rotations within a PVD chamber.

[0052] Chamber in high vacuum (10 -2 The plasma was pumped down to less than Pa and heated to approximately 450-550°C by a heater located inside the chamber. The blank was then etched in Ar plasma for 60 minutes.

[0053] First, 0.50 Al 0.50 By using only the target, Ti 0.50 Al 0.50 The innermost layer of N was deposited.

[0054] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -50 V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150 A for 70 minutes (each) (two flanges). The table rotation speed was 5 rpm. Ti with a thickness of approximately 1.4 μm. 0.50 Al 0.50 A layer of N was deposited on the blank.

[0055] Next, tire 0.85 Si 0.15 Target and Ti 0.20 Al 0.80 By alternating the use of targets, nanolayers are deposited, resulting in a Ti layer approximately 35 nm thick. 0.85 Si 0.15 N / Ti 0.20 Al 0.80 The first sequence of N nanolayers was generated. The table rotation speed was 5 rpm. Then Ti 0.50 Al 0.50 Using only the target, a Ti with a thickness of approximately 35nm 0.50 Al 0.50 N layers were generated. This procedure is Ti 0.50 Al 0.50 Nanolayer Ti combined with a "single layer" of N 0.85 Si 0.15 N and Ti 0.20 Al 0.80 The process was repeated until 20 sequences of the N nanolayer sequence were completed. The total thickness of the deposited nanolayer was approximately 1.4 μm.

[0056] The chamber pressure (reaction pressure) is set to 4 Pa ​​with N2 gas, and Ti 0.85 Si 0.15 and Ti 0.20 Al 0.80 When using a target, apply a DC bias voltage of -40V (relative to the chamber wall) to the Ti 0.50 Al 0.50When using a target, a DC bias voltage of -80V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150A for 70 minutes each (two flanges at a time). The table rotation speed was 5 rpm. A nanomultilayer coating with a thickness of approximately 1.4 μm was deposited on the blank.

[0057] The rotation speed correlates with the thickness of a particular stage, and the current deposition rate and the table rotation speed of 5 rpm for the equipment used correlate with each nanolayer Ti 0.85 Si 0.15 N and Ti 0.20 Al 0.80 It was concluded that this correlates with the average individual nanolayer thickness of N, which is approximately 2 nm.

[0058] Finally, to obtain a uniform color among the individually coated cutting tools that were fabricated, Ti 0.85 Si 0.15 By using only the target, Ti 0.85 Si 0.15 The outermost layer of N was deposited. All deposition parameters were the same as when depositing the previous layer (one flange), except that the bias was -60V and the cathode was operated for 10 minutes. 0.85 Si 0.15 A layer of N was deposited to a thickness of approximately 0.2 μm.

[0059] The coated cutting tool is referred to as "Sample 2 (comparison)".

[0060] Example 3 Ti 0.80 Si 0.20 N nanolayer and Ti 0.40 Al 0.60 N nanolayers and high Al Ti deposited on sintered cemented carbide cutting tool insert blanks of the shapes CNMG120408MM and R390-11T308M-PM, respectively. 0.25 Al 0.75 N, Ti 0.15 Al 0.85 N, or Ti 0.05Al 0.95 Three different sets of samples of coated cutting tools containing nanomultilayers with one of the N nanolayers were provided. The cemented carbide composition was 10 wt% Co, 0.4 wt% Cr, and residual WC. The cemented carbide blanks were coated by cathode arc evaporation in a vacuum chamber containing four arc flanges (each flange containing multiple cathode evaporators). 0.80 Si 0.20 The target was installed inside the evaporator at two of the opposing flanges. The remaining target was Ti 0.40 Al 0.60 and the high-Al (Ti,Al) target used (Ti in three different operations) 0.25 Al 0.75 Ti 0.15 Al 0.85 , or Ti 0.05 Al 0.95 The targets were mounted inside the evaporator on the remaining two flanges, which faced each other. The targets were circular and planar, with a diameter of 100 mm, which is commonly available on the market. Suitable target technology packages for arc evaporation are available from market suppliers such as IHI Hauzer Techno Coating BV, Kobelco (Kobe Steel Ltd.), and Oerlikon Balzers.

[0061] An uncoated blank was mounted on a pin that underwent three rotations within a PVD chamber.

[0062] Chamber in high vacuum (10 -2 The plasma was pumped down to less than Pa and heated to approximately 450-550°C by a heater located inside the chamber. The blank was then etched in Ar plasma for 60 minutes.

[0063] First, 0.40 Al 0.60 By using only the target, Ti 0.40 Al 0.60The innermost layer of N was deposited. The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -70 V (relative to the chamber wall) was applied to the blank assembly. The cathode was operated in arc discharge mode with a current of 150 A for 100 minutes (each flange). The table rotation speed was 5 rpm. Ti with a thickness of approximately 1 μm. 0.40 Al 0.60 A layer of N was deposited on the blank.

[0064] Next, nanolayers were deposited by using all of the attached targets.

[0065] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -100V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150A for 50 minutes each (four flanges). The table rotation speed was 5 rpm. A nanomultilayer coating with a thickness of approximately 2 μm was deposited on the blank.

[0066] Since the table rotation speed correlates with the thickness of a particular stage, the current deposition rate and the table rotation speed of 5 rpm for the equipment used result in each nanolayer Ti in the three different nanolayers fabricated. 0.40 Al 0.60 N, Ti 0.80 Si 0.20 N, as well as Ti 0.25 Al 0.75 N, Ti 0.15 Al 0.85 N and Ti 0.05 Al 0.95 It was concluded that there is a correlation with the average individual nanolayer thickness of approximately 2 nm for each of N. The number of nanolayers in all three different sets of nanomultilayers is approximately 1000.

[0067] The nanomultilayer of the first set of samples is Ti 0.40 Al 0.60 N / Ti 0.80 Si 0.20 N / Ti 0.25 Al0.75 N / Ti 0.80 Si 0.20 The nanolayers of the second set of samples include a repeating sequence of continuous nanolayers in the order of N. 0.40 Al 0.60 N / Ti 0.80 Si 0.20 N / Ti 0.15 Al 0.85 N / Ti 0.80 Si 0.20 The nanolayers of the third set of samples include a repeating sequence of continuous nanolayers in the order of N. 0.40 Al 0.60 N / Ti 0.80 Si 0.20 N / Ti 0.05 Al 0.95 N / Ti 0.80 Si 0.20 The sequence includes repeating sequences of continuous nanolayers in the order N.

[0068] Finally, to obtain uniform color across the individually coated cutting tools fabricated, the outermost layer was deposited by using only the respective high-Al (Ti,Al) targets used when depositing each nanolayer for the three different sets of samples. All deposition parameters were the same as when depositing the previous layer (one flange), except that the bias was -100V and the cathode was operated for 10 minutes. 0.25 Al 0.75 N, Ti 0.15 Al 0.85 N, or Ti 0.05 Al 0.95 Layers of N were deposited on three different sets of samples, each to a thickness of approximately 0.2 μm.

[0069] In a nanomultilayer, each nanolayer Ti 0.40 Al 0.60 N, Ti 0.85 Si 0.15 N, and also Ti 0.25 Al 0.75 N, Ti 0.15 Al 0.85 N and Ti 0.05 Al 0.95The sum of the thickness ratios of each of the thicknesses of N, i.e., Ti 0.40 Al 0.60 N:Ti 0.85 Si 0.15 N:(Ti 0.25 Al 0.75 N, Ti 0.15 Al 0.85 N, or Ti 0.05 Al 0.95 N) is approximately 1:2:1. This ratio is estimated from the assumed equal deposition rates from each target, rotation during deposition, and deposition time.

[0070] The coated cutting tools that were fabricated are referred to as follows: - Nanomultilayer, Ti 0.80 Si 0.20 N, Ti 0.40 Al 0.60 N and Ti 0.25 Al 0.75 Sample 3, a coated cutting tool composed of N nanolayers. - Nanomultilayer, Ti 0.80 Si 0.20 N, Ti 0.40 Al 0.60 N and Ti 0.15 Al 0.85 Sample 4, a coated cutting tool composed of a nanolayer of N. - Nanomultilayer, Ti 0.80 Si 0.20 N, Ti 0.40 Al 0.60 N and Ti 0.05 Al 0.95 "Sample 5" is a coated cutting tool composed of a nanolayer of N.

[0071] Example 4 Ti deposited on sintered cemented carbide cutting tool insert blanks of the shapes CNMG120408MM and R390-11T308M-PM 0.80 Si 0.20 N, Ti 0.40 Al 0.60 N and Ti 0.25 Al0.75 We provided a cutting tool coated with a nanolayer containing N nanolayers. The cemented carbide composition was 10 wt% Co, 0.4 wt% Cr, and the residue WC. The cemented carbide blank was coated by cathode arc evaporation in a vacuum chamber containing four arc flanges (each flange containing multiple cathode evaporators). 0.80 Si 0.20 The target was installed inside the evaporator at two of the opposing flanges. The remaining target was Ti 0.40 Al 0.60 and Ti 0.25 Al 0.75 The targets were mounted inside the evaporator on the remaining two flanges, which faced each other. The targets were circular and planar, with a diameter of 100 mm, which is readily available on the market. Suitable target technology packages for arc evaporation are available from market suppliers such as IHI Hauzer Techno Coating BV, Kobelco (Kobe Steel Ltd.), and Oerlikon Balzers.

[0072] An uncoated blank was mounted on a pin that underwent three rotations within a PVD chamber.

[0073] Chamber in high vacuum (10 -2 The plasma was pumped down to less than Pa and heated to approximately 450-550°C by a heater located inside the chamber. The blank was then etched in Ar plasma for 60 minutes.

[0074] First, 0.40 Al 0.60 and Ti 0.25 Al 0.75 By using only the target, Ti 0.40 Al 0.60 N and Ti 0.25 Al 0.75 The innermost layer, which is a nanolayer with N nanolayers, was deposited.

[0075] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -100V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150A for 50 minutes each (two flanges). The table rotation speed was 5 rpm. Ti with a thickness of approximately 1 μm. 0.40 Al 0.60 N and Ti 0.25 Al 0.75 A nanolayer of N was deposited on a blank. Since the current deposition rate and, in the case of the equipment used, the rotation speed correlate with the thickness of a particular stage, it was concluded that the average individual nanolayer thickness was approximately 2 nm.

[0076] Next, by using all the attached targets, Ti 0.80 Si 0.20 N, Ti 0.40 Al 0.60 N and Ti 0.25 Al 0.75 A nanolayer structure with N nanolayers was deposited.

[0077] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -100V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150A for 50 minutes each (four flanges). The table rotation speed was 5 rpm. A nanomultilayer coating with a thickness of approximately 2 μm was deposited on the blank.

[0078] The rotation speed correlates with the thickness of a particular stage, and the current deposition rate and the table rotation speed of 5 rpm for the equipment used correlate with each nanolayer Ti 0.40 Al 0.60 N, Ti 0.80 Si 0.20 N and Ti 0.25 Al 0.75 It was concluded that there is a correlation with the average individual nanolayer thickness of N, which is approximately 2 nm. The number of nanolayers in a nanomultilayer is approximately 1000.

[0079] Nano multilayers are made of Ti0.40 Al 0.60 N / Ti 0.80 Si 0.20 N / Ti 0.25 Al 0.75 N / Ti 0.80 Si 0.20 The sequence includes repeating sequences of continuous nanolayers in the order N.

[0080] Finally, to obtain a uniform color among the individually coated cutting tools that were fabricated, Ti 0.25 Al 0.75 By using only the target, Ti 0.25 Al 0.75 The outermost layer of N was deposited. All deposition parameters were the same as when depositing the previous layer, and the cathode was operated for 10 minutes (one flange). Ti 0.25 Al 0.75 A layer of N was deposited to a thickness of approximately 0.2 μm.

[0081] In the three nanolayer types of nanomultilayers, each nanolayer Ti 0.40 Al 0.60 N, Ti 0.80 Si 0.20 N, Ti 0.25 Al 0.75 The sum of the thickness ratios of each thickness N, i.e., Ti 0.40 Al 0.60 N:Ti 0.80 Si 0.20 N:Ti 0.25 Al 0.75 N is approximately 1:2:1. This ratio is estimated from the assumed equal deposition rates from each target, rotation during deposition, and deposition time.

[0082] The coated cutting tool is referred to as "Sample 6".

[0083] Example 5 Ti deposited on sintered cemented carbide cutting tool insert blanks of the shapes CNMG120408MM and R390-11T308M-PM 0.80 Si 0.20 N, Ti 0.40 Al 0.60N and Ti 0.15 Al 0.85 We provided a cutting tool coated with a nanolayer containing N nanolayers. The cemented carbide composition was 10 wt% Co, 0.4 wt% Cr, and the residue WC. The cemented carbide blank was coated by cathode arc evaporation in a vacuum chamber containing four arc flanges (each flange containing multiple cathode evaporators). 0.15 Al 0.85 The two targets were mounted inside the evaporator on two of the opposing flanges. The remaining target was Ti 0.40 Al 0.60 and Ti 0.80 Si 0.20 The targets were mounted inside the evaporator on the remaining two flanges, which faced each other. The targets were circular and planar, with a diameter of 100 mm, which is readily available on the market. Suitable target technology packages for arc evaporation are available from market suppliers such as IHI Hauzer Techno Coating BV, Kobelco (Kobe Steel Ltd.), and Oerlikon Balzers.

[0084] An uncoated blank was mounted on a pin that underwent three rotations within a PVD chamber.

[0085] Chamber in high vacuum (10 -2 The plasma was pumped down to less than Pa and heated to approximately 450-550°C by a heater located inside the chamber. The blank was then etched in Ar plasma for 60 minutes.

[0086] First, 0.40 Al 0.60 By using only the target, Ti 0.40 Al 0.60 The innermost layer of N was deposited.

[0087] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -70 V (relative to the chamber wall) was applied to the blank assembly. The cathode was operated in arc discharge mode with a current of 150 A for 100 minutes (one flange each). The table rotation speed was 5 rpm. Ti with a thickness of approximately 1 μm. 0.40 Al 0.60 A layer of N was deposited on the blank.

[0088] Next, nanolayers were deposited by using all of the attached targets.

[0089] The chamber pressure (reaction pressure) was set to 4 Pa ​​with N2 gas, and a DC bias voltage of -100V (relative to the chamber wall) was applied to the blank assembly. The cathodes were operated in arc discharge mode with a current of 150A for 50 minutes each (four flanges). The table rotation speed was 5 rpm. A nanomultilayer coating with a thickness of approximately 2 μm was deposited on the blank.

[0090] The rotation speed correlates with the thickness of a particular stage, and the current deposition rate and the table rotation speed of 5 rpm for the equipment used correlate with each nanolayer Ti 0.40 Al 0.60 N, Ti 0.80 Si 0.20 N and Ti 0.15 Al 0.85 It was concluded that there is a correlation with the average individual nanolayer thickness of N, which is approximately 2 nm. The number of nanolayers in a nanomultilayer is approximately 1000.

[0091] Nano multilayers are made of Ti 0.15 Al 0.85 N / Ti 0.40 Al 0.60 N / Ti 0.15 Al 0.85 N / Ti 0.80 Si 0.20 The sequence includes repeating sequences of continuous nanolayers in the order N.

[0092] Finally, to obtain a uniform color among the individually coated cutting tools that were fabricated, Ti 0.15 Al 0.85 By using only the target, Ti 0.15 Al 0.85 The outermost layer of N was deposited. All deposition parameters were the same as when depositing the previous layer, and the cathode was operated for 10 minutes (one flange). Ti 0.15 Al 0.85 A layer of N was deposited to a thickness of approximately 0.2 μm.

[0093] The coated cutting tool is referred to as "Sample 7".

[0094] In a nanomultilayer, each nanolayer Ti 0.40 Al 0.60 N, Ti 0.80 Si 0.20 N, Ti 0.15 Al 0.85 The sum of the thickness ratios of each thickness N, i.e., Ti 0.40 Al 0.60 N:Ti 0.80 Si 0.20 N:Ti 0.15 Al 0.85 N is approximately 1:1:2. This ratio is estimated from the assumed equal deposition rates from each target, rotation during deposition, and deposition time.

[0095] Samples 1-7 that were prepared are listed in Table 1. TIFF0007940004000001.tif151170

[0096] Table 2 further summarizes samples 1-7. TIFF0007940004000002.tif139170

[0097] Example 6 A cutting test was performed to determine the performance of the prepared sample.

[0098] Explanation of terms used: The following expressions / terms are commonly used in metal cutting and are explained in the table below: V c (m / min): Cutting speed in meters per minute f z (mm / edge): Feed rate in millimeters per edge (in milling) f n (mm / rev): Feed rate per revolution (in turning) z: (Number) Number of edges on the cutting tool a e (mm): Radial depth of cut in millimeters a p (mm): Axial depth of cut in millimeters

[0099] Flank wear test: Longitudinal turning Workpiece material: Sverker 21 (tool steel), hardness about 210HB, D=180, L=700mm V c =125m / min f n =0.072mm / rev a p =2mm No cutting fluid

[0100] The cutoff criterion for tool life is a flank wear VB of 0.15mm.

[0101] Peeling resistance: The evaluation was carried out by a turning test on austenitic stainless steel. In order to cause adhesive wear and coating peeling, the depth of cut a (in one operation during radial facing) p was varied between 4~0mm and 0~4mm. The insert was evaluated by SEM analysis.

[0102] Operation: Facing (turning) Workpiece material: Austenitic stainless steel bar Sanmac 316L, L=200mm, D=100mm, about 215HB Insert type: CNMG120408MM Cooling: Yes Cutting depth a p = 4~0mm, 0~4mm Cutting speed V c =140m / min Feed rate f z =0.36mm / rev TIFF0007940004000003.tif125170

[0103] It can be concluded that samples 1, 3, 4, 6, and 7 within the present invention have high flank wear resistance and exhibit far less flank wear than comparative samples 2 and 5 outside the present invention.

[0104] It can be concluded that samples 1, 3, 4, 6, and 7 within the present invention have high peel resistance and function far better than comparative sample 2 outside the present invention.

[0105] Alternative inner layer effects: Samples 3 and 6 differ in that sample 6 has an internal (Ti,Al)N nanolayer rather than a single (Ti,Al)N layer. Further cutting tests were performed on samples 3 and 6 to determine the effect of the alternative inner layer in sample 6 on comb-like crack resistance and cutting edge toughness.

[0106] Crack resistance: Operation: Shoulder milling Tool holder: C5-391.20-25080 Material of workpiece: Toolox33 (tool steel), L=600mm, I=200mm, h=100mm Insert type: R390-11T308M-PM Cutting speed V c =250m / min Feed rate f z =0.2mm / rev Cutting depth a p =3mm Radial fitting a e = 12.5 mm Cutting fluid included

[0107] The criterion for the end of tool life is a maximum chipping height VB > 0.3 mm.

[0108] Cutting edge toughness: Material of the workpiece: Dievar unhardened, P3.0.Z.AN z=1 V c =200m / min f z = 0.20 mm a e = 12mm a p =3.0 Cutting length = 12mm No cutting fluid

[0109] The cutoff criteria are that the chipping along the cutting edge is at least 0.5 mm, or that the measured depth in either the relief or rake phase is 0.2 mm. Tool life is presented as the number of cutting entry points required to achieve these criteria. TIFF0007940004000004.tif49170

[0110] The results of both the comb crack resistance test and the edge line toughness (ELT) test showed that the inner Ti 0.40 Al 0.60 Instead of the N layer, the inner nano-multi-Ti 0.40 Al 0.60 N / Ti 0.25 Al 0.75 This is improved by the presence of N layers.

Claims

1. A coated cutting tool (1) comprising a substrate (5) and a coating (6), wherein the coating (6) comprises Ti 1-x Al x N (0.35≦x<0.67) as a first nanolayer type (9), Ti 1-y Si y N (0.10≦y≦0.25) as a second nanolayer type (10), and Ti 1-z Al z N (0.70≦z≦0.90) as a third nanolayer type (11), the coating comprising a nanomultilayer (8) of about 0.5 to about 10 μm formed of alternating nanolayers of the foregoing types, wherein the average nanolayer thickness of each of the nanolayer types Ti 1-x Al x N (9), Ti 1-y Si y N (10), and Ti 1-z Al z N (11) in the nanomultilayer (8) is 1 to 30 nm, the coated cutting tool (1).

2. The ratio between the total thicknesses of all nanolayer types in the nanomultilayer (8), Ti 1-x Al x N(9): Ti 1-y Si y N(10): Ti 1-z Al z The coated cutting tool (1) according to claim 1, wherein N(11) is a:b:c [wherein 0.5 < a < 3, 0.5 < b < 3, 0.5 < c < 3].

3. The first nanolayer type (9) is Ti 1-x Al x The coated cutting tool (1) according to claim 1, wherein if N is the case, 0.40 ≤ x ≤ 0.

67.

4. The second nanolayer type (10) is Ti 1-y Si y The coated cutting tool (1) according to claim 1, wherein if N is true, then 0.13 ≤ y ≤ 0.

23.

5. The third nanolayer type (11) is Ti 1-z Al z The coated cutting tool (1) according to claim 1, wherein if N is the case, 0.70 < z ≤ 0.

85.

6. Each nanolayer type Ti in nanomultilayers 1-x Al x N, Ti 1-y Si y N, and Ti 1-z Al z The coated cutting tool (1) according to claim 1, wherein the average nanolayer thickness in the nanomultilayer (8) of N is 1 to 20 nm.

7. Nanolayer type Ti in nanomultilayers 1-x Al x N(9), Ti 1-y Si y N(10), and Ti 1-z Al z One of N(11) and nanolayer type Ti 1-x Al x N(9), Ti 1-y Si y N(10), and Ti 1-z Al z The coated cutting tool (1) according to claim 1, wherein the ratio of the average nanolayer thickness in the nanolayer (8) to any of the remaining two of N(11) is 0.1 to 10.

8. In a nanolayer (8), within a series of 10 consecutive nanolayers, nanolayer type Ti 1-x Al x N(9), Ti 1-y Si y N(10), and Ti 1-z Al z A coated cutting tool (1) according to claim 1, wherein all of N(11) are present.

9. The coated cutting tool (1) according to claim 1, wherein the thickness of the nanolayer (8) is approximately 1 to approximately 8 μm.

10. The coated cutting tool (1) according to claim 1, wherein the coating (6) includes an inner layer (7) of TiN or (Ti,Al)N having a thickness of about 0.1 to 3 μm below the nearest nanolayer (8) of the substrate (5).

11. The inner layer (7) is Ti 1-t Al t A coated cutting tool (1) according to claim 10, wherein N (0.35 ≤ t ≤ 0.70).

12. The inner layer (7) is Ti 1-u Al u N (0.35 ≤ u < 0.67) and Ti 1-v Al v A coated cutting tool (1) according to claim 10, wherein the (Ti,Al)N layer is a (Ti,Al)N nanomultilayer of alternating N (0.70 ≤ v ≤ 0.90) nanolayers.

13. The coated cutting tool (1) according to claim 1, wherein the base material (5) of the coated cutting tool (1) is selected from the group consisting of cemented carbide, cermet, ceramic, cubic boron nitride, and high-speed steel.

14. The coated cutting tool (1) according to claim 1, wherein the coated cutting tool (1) is a cutting tool insert, drill, or solid end mill for metal machining.

Citation Information

Patent Citations

  • Composite coated cutting tool containing periodic coating and preparation method thereof

    CN102242338A

  • Hard film coated tool

    JP2000334606A

  • Multilayer nitride hard coating

    JP2013528252A

  • TiAlN coated tools

    JP2015529571A

  • Imprint device and manufacturing method of material

    JP2016111201A